How accurate are the inflation forecasts published by the commercial banks? - Ólafsdóttir, Katrín; Sigurðsson, Kári (Tímarit um viðskipti og efnahagsmál, 2010)
The paper evaluates monthly inflation forecasts of four financial entities during the period 2000 to 2006. Most of the forecasts show similar results with inflation forecasts 2 to 6 points under the actual change in inflation each month. There is no statistical difference in the quality of forecasts between periods, that is a good forecast in one month does not imply a good forecast in the following month. In the beginning of each month during the research period each financial entity published a forecast of inflation for that month, while Statistics Iceland would publish the official inflation figure around the 10th day of the month. Icelandic bonds are linked to inflation and during the ten day period before the official inflation figure is published, the index used was the Central Bank‘s quarterly forecast smoothed over three months. This paper examines whether there is arbitrage opportunity in using the inflation forecasts in bond transactions. Although the monthly inflation forecasts are usually better than the smoothed Central Bank‘s quarterly forecasts, arbitrage opportunities are slim due to transactions costs. Í rannsókn þessari er metinn árangur fjögurra aðila í gerð mánaðarlegrar verðbólguspár á árunum 2000 til 2006. Flestar spárnar eru nokkuð svipaðar og í þeim er verðbólga að meðaltali vanmetin um tvo til sex punkta. Ekki mælast tölfræðilega marktæk tengsl milli þess hversu áreiðanlegar spárnar eru eftir tímabilum, þ.e. aðili sem spáir vel einn mánuðinn er ekki líklegri en annar til að spá vel í næsta mánuði. Við upphaf hvers mánaðar spá aðilar á markaði fyrir um verðbólgumælingu Hagstofunnar í viðkomandi mánuði en á rannsóknartímanum birti Hagstofan verðbólgumælingu í kringum 10. hvers mánaðar. Oftast eru spárnar betri en verðbótaþátturinn sem notaður var til að uppreikna verðtryggingu íslenskra skuldabréfa í upphafi mánaðar áður en verðbólgumæling Hagstofunnar birtist. Í greininni er kannað hvort hægt sé að færa sér þetta í nyt með skuldabréfaviðskiptum samkvæmt verðbólguspá áður en ...